Road To Progress or Bumpy Detour? Jeepney Drivers’ Lived Experiences Amidst Ongoing Phaseout - Lacsina, Reignchielle Jcynd D (Animo Repository, 2024)
This study utilizes a phenomenological research design to explore the lived experiences of jeepney drivers amidst the ongoing government’s initiative to phase out and modernize traditional jeepneys in the Philippines. It focused on six jeepney drivers operating in the Tarlac public transportation system, selected based on specific inclusion criteria. The Theory of Change was used to delve deeper into the findings, revealing that the government's initiatives have challenged the stability of jeepney drivers’ livelihood during the modernization transition. Their lives were in jeopardy due to this abrupt transformation. It left them powerless to adapt to the changes or boycott. The drivers have mixed recommendations. Some are willing to comply as long as the government considers affordable transportation options, supports local manufacturers, and further analyzes the directives. Others are calling to cease the initiatives. The government initiative is stuck between the “Change” and “Refreezing” stages. The persistent restraining forces identified—financial barriers, inequitable support, and lack of trust in policy implementation—underscore the critical need for targeted interventions. Unless these issues are addressed, resistance and destabilization will persist and get worse.